2022
DOI: 10.3390/su14137803
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms Effect on Microbial Population and Soil Fertility as Well as Their Interaction with Agriculture Practices

Abstract: Earthworms mix soil layers and bind the soil with organic matter. This combination allows organic matter to disperse through the soil and also allows plants to access the nutrients they retains and enhance the soil’s fertility. Earthworms improve the soil’s biological, chemical, and physical characteristics and serve as soil conditioners. They do so by dissolution, aeration, soil organic breakdown, the release of plant nutrients, and their role in the fastening of nitrogen due to plant growth hormone secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 70 publications
1
30
0
1
Order By: Relevance
“…Many measures or facts that violate traditional biodiversity protection, such as the use of chemical fertilizers and pesticides, and soil disturbance caused by cultivation, must be included in the human management of cultivated land (Wang, 2022). Tillage practices are inadequate for soil worms but good for soil accessibility to roots, weed control, and increased crop yields (Ahmed and Al-Mutairi, 2022). In particular, intensification of land use, crop rotation and crop species, fertilizers and pH, the type and frequency of periodic tillage, pesticide application, and pollution (ecotoxicological studies) are the main driving forces influencing biodiversity in agricultural soils (Aksoy et al, 2017).…”
Section: Understanding and Managing Soil Biodiversitymentioning
confidence: 99%
“…Many measures or facts that violate traditional biodiversity protection, such as the use of chemical fertilizers and pesticides, and soil disturbance caused by cultivation, must be included in the human management of cultivated land (Wang, 2022). Tillage practices are inadequate for soil worms but good for soil accessibility to roots, weed control, and increased crop yields (Ahmed and Al-Mutairi, 2022). In particular, intensification of land use, crop rotation and crop species, fertilizers and pH, the type and frequency of periodic tillage, pesticide application, and pollution (ecotoxicological studies) are the main driving forces influencing biodiversity in agricultural soils (Aksoy et al, 2017).…”
Section: Understanding and Managing Soil Biodiversitymentioning
confidence: 99%
“…Earthworms are currently the subject of the most investigation in studies on the cooperative restoration of animals and plants. Earthworms can both increase soil fertility and encourage plant root growth (43). Hexavalent chromium was removed from contaminated soil using a combination of bacteria, sludge, and straw (44), and the findings indicated that 1% straw plus 1% Compound bacteria and 30% sludge together reduce soil chromium by 96.6%, and this combination can provide the greatest effect.…”
Section: Joint Remediationmentioning
confidence: 99%
“…They are referred to be the farmer's friend and can be anything from a few microns to one or two metres in length (Phillips et al, 2021). Many studies on the impacts of earthworms on soil fertility, structure, and crop growth came to the conclusion that burrowing, casting, and other earthworm activities improved the soil's physico-chemical condition (Ahmed et al, 2022;Syers 1984; Reddy and Pasha 1993).…”
Section: Introductionmentioning
confidence: 99%